A Semiótica na primeira parte do Evangelho de João - Nina, Ronaldo Contin Della (2022)
This research understood and deepened through the method of collecting information, based on secondary sources, the study of semiotics applied in the Fourth Gospel and as a starting point, the application of signs, in which semiotics, because it is the study of the construction of meaning , the study of the sign process and the meaning of communication, will lead to its application in the Book of Signs (Jn 1,19 to 12,50), within the framework of the Gospel according to John. With the intention of taking the concepts and understanding of semiotics, which aims to study the forms, types, systems of signs and the effects of the use of signs, signs, indications, symptoms or symbols, in the forms of representation used to convey feelings, thoughts, ideas and ideologies. Such an analysis will lead to the relevance of this pericope (Jn 2,1-11) within the Book of Signs of the Gospel according to John. The recurrence of the term sign in the Johannine text will be presented, organized into seven signs, so that the text of the “Transformation of water into wine at Cana” summarizes the understanding by his disciples who believed in Jesus. A semiotic analysis is applied to each of the seven signs, pointing to the Messiah in the accomplishments of his works and, also, to whom the message is destined in each of the signs. So in the Fourth Gospel these actions, that is, Jesus' public life, are marked by signs. Our proposal is to analyze the semantic field of signs and their articulation in the narrative plot from the Johannine perspective